Booking in the rain: Testing the impact of public information on prices - Paolo Figini; Simona Cicognani; Lorenzo Zirulia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
The key role played by public information in market economies is paramount. Yet, investigation on how prices are affected is hindered by intricate endogeneity and parametrization issues. This paper contributes to the literature by identifying and studying a case where public information is related to weather forecasts, in a sector (tourism) where meteorological conditions exogenously impact on both suppliers' and consumers' decisions, especially in leisure destinations. We first develop a theoretical model where forecasts affect demand and hence equilibrium prices in accommodation: an improvement in the weather forecast has a positive impact on the price, the effect being stronger the higher the level of accuracy of the forecast and the level of ex ante uncertainty in weather conditions. We then estimate an augmented hedonic price model where dynamic characteristics (typical of advanced booking strategies) are included together with information about weather forecasts. Consistent with the theory, we find that, ceteris paribus, good weather forecasts are associated to higher prices, the impact being larger the higher their level of accuracy and the higher the ex ante level of uncertainty in weather conditions.
Keywords: D80; D22; L83; 330; Information uncertainty; Bayesian model; Big Data; Pricing strategy; Exogenous quality; Hotels; Weather forecast; Hedonic price